Analisis Parameter Karbon Monoksida (CO) dari Aktivitas Transportasi di Sekitar Industri Pertambangan Nikel: Studi Kasus: Jalan Poros Puuruy-Morosi, Desa Puuruy, Kecamatan Morosi, Kabupaten Konawe - Ashar, Muhammad; Sumarlin, Sumarlin; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Outdoor air contamination comes from a moving source of smoke and smoke from burning vehicles such as motorcycles, cars, buses, trucks. Morosi subdistrict is an industrial area who populated by several mineral purification companies. The company certainly has considerable human resources, in which many workers use vehicles to optimize work time. Worker mobility becomes a contributor to increased burning, leftover air pollution from the transport known as carbon monoxide. Monitoring the number of carbon monoxide (CO) pollutants will be necessary in view of future effects. The CO Level measures were performed with a measuring procedure referring to the Indonesian National Standard is 19-7117.10-2005, in use of portable carbon monoxide meters. This research indicated at the morning concentration levels of gas CO on the axle road Puuruy-Morosi reached 8000 μg/Nm3 and by midday it reached 5000 μg/ nm3 and the CO concentration it’s still safe for human. But in the afternoon the CO concentration increased and reached 15000 μg/Nm3 exceeds the air quality standard of 15000 μg/Nm3.